Effectiveness of medicinal plants extracts in the in vitro control of Candida albicans (Research, Society and Development, 2022)
Fungal diseases after diagnosis are treated with different antimicrobial agents, however, resistant strains have appeared. Faced with the emergence of Candida strains resistant to synthetic antifungal agents, it was observed that the use of medicinal plants capable of inhibiting the growth of these microorganisms has been the subject of studies. Thus, scientific investigation of the properties of essential oils and plant extracts has been carried out in search of an equivalent satisfactory level and a lower rate of disadvantages or side effects. The objective was to evaluate the effectiveness of plant extracts in inhibiting the growth of Candida albicans. Three clinical strains of C. albicans and standard C. albicans ATCC 25923 were used. To obtain the extracts rue, rosemary, neem and citronella leaves were used. Hydroalcoholic extraction was carried out in 70% ethanol. Minimum inhibitory concentration (MIC), minimum fungicidal concentration (MFC) and viability against the different extracts were determined. C. albicans ATCC 25923 strains and clinics showed susceptibility to the different extracts. The extracts showed the ability to cancel the growth of C. albicans at different times, however they showed efficacy in the control this yeast.The results obtained reveal that rosemary, rue, citronella and neem plants can be a potential source of new antifungal agents for the control of Candida albicans.